Outcomes of perineal reconstruction with inferior gluteal artery myocutaneous flaps and primary closure following abdominoperineal resection. Issue 11 (23rd May 2022) - Gultekin, Sinem; Gartrell, Richard; Lu, Lucy; Croxford, Matthew; Faragher, Ian; Chan, Steven T. F.; Yeung, Justin M. C.
Abstract: Background: Perineal wound morbidity following abdominoperineal resection (APR) is a significant challenge. Myocutaneous flap‐based techniques have been developed to overcome morbidity associated with perineal reconstruction. We reviewed outcomes for patients undergoing APR in a hospital that performs inferior gluteal artery myocutaneous (IGAM) island transposition flaps and primary closure (PC) for perineal reconstruction. Methods: A retrospective study of patients who underwent APR for malignancy between January 2012 and March 2020 was performed and outcomes between IGAM reconstruction and PC compared. Primary outcomes were wound infection and dehiscence. Secondary outcomes included return to theatre, operative time, length of stay, flap loss and perineal hernia incidence. Results: One‐hundred and two patients underwent APR, with 50 (49%) who had PC and 52 (51%) had IGAM flap reconstructions. There were no differences between each group with regards to wound infection (23 vs. 22%, P = 0.55) or wound dehiscence (25 vs. 24%, P = 0.92). Thirteen (25%) IGAM patients required a return to theatre compared to three PC patients (6%) ( P = 0.008). IGAM procedures required twice the overall operative time (506 vs. 240 min, P = 0.001) with no differences between groups when comparing the APR component (250 vs. 240 min, P = 0.225). The IGAM group had a longer length of stay (median 13 days vs. 9 days, P = 0.001). Only one IGAM flap was lost and no symptomatic hernias were identified. Conclusion: Perineal closure technique did not affect the incidence of wound infection or dehiscence. Closure technique should be tailored to underlying patient characteristics and surgical pathology. Abstract : We reviewed outcomes for patients undergoing APR in a hospital that performs inferior gluteal artery myocutaneous (IGAM) island transposition flaps and primary closure (PC) for perineal reconstruction.